Hepatobiliary complications of hydatidosis: Relato - Porras, Yamandú (Cirugía del Uruguay, 1973)
This report is based on 129 cases of liver echinococosis. Pre and post-operatory study has not enabled us to establish a clearly marked delimitation beaween complicated and non .complicated hydatid cyst. The term deemed most correct is "repercussion" on the different structures. There was repercussion on the biliary tract in 38.7 % of cases. 'Ibere is no hydatid cirrhosis but rather it should be considered as fibrosis. Surgical treatment consists of cystostomy. In supurated cases drainage should be rapid. This also applies to jaundieed forms of cholansitis. Repercussion of hydatid cyst on vascular system appears as compression or thrombosis of portal or suprahepatic veins. Hepatobiliary complications are defined as direct or indirect aggression of liver parenchima and it becomes necessary to prescribe surgical treatment directed fundamentally towards the. hepatobiliary sector in its broadest sense.